Effect of Fe addition on glass-forming ability, thermal stability of B2 CuZr phase and crystallization kinetics for CuZr-based amorphous alloys - Ziyan Hao (Elsevier, 2021)
The glass-forming ability (GFA), thermal stability and crystallization kinetics of (Cu0.5Zr0.5)100-xFex (x = 2.5, 5, 7.5, 10 and 12.5 at.%) amorphous alloys were studied in detail. As Fe concentration increases, the GFA and thermal stability decrease first and then increase. The excessive Fe addition significantly deteriorates the GFA due to the precipitation of the FeZr2 phase. Interestingly, with increasing Fe concentration, the crystallization products gradually transit from Cu10Zr7 and CuZr2 to B2 CuZr phase, indicating that Fe addition can effectively enhance the thermal stability of B2 phase. Simulation results show that Fe atoms may be dissolved into the B2 lattice substituting Cu sites and decrease the formation energy, which is similar to Co–or Zn-added CuZr-based alloys. Non-isothermal crystallization behaviors of Cu–Zr–Fe amorphous alloys are well described by the Šesták-Berggren (SB) model instead of the John-Mehl-Avrami (JMA) model due to the multi-phase formation (low Fe concentration) or the nucleation and growth of B2 phase (high Fe concentration). These results could help with the understanding of further stabilizing B2 CuZr phase and the fabrication of high-performance CuZr-based composites.